Digitalisasi Laporan Keuangan UMKM di Kota Bogor Menggunakan Microsoft Excel dan Manager.io - Khairiyah, Nabila; Putri , Amanda; Pitaloka, Calya Sekar Arum; Rasul , Nabilah Hanun Muthmainnah; Sella, Nadra Asmira; Fitriyani, Aulia Fitriyani; Pranowo, Bianca Alika; Wiratmadhi, I Putu Dimas; Oktrivina, Amelia (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
It is essential for micro, small, and medium enterprises to have an organized and accurate financial recording system. However, practical observations show that many MSMEs still rely on manual bookkeeping methods that are unstructured and prone to error. Toko Bungbu Baraya, one of the culinary business units of PT Selaras Rasakoe Indonesia, served as the subject of this study. The aim of the research is to develop a digital financial recording system based on Manager.io and Microsoft Excel. This study employed a qualitative approach involving participatory observation and structured interviews with store employees. The research was conducted in July 2025 over a two-week period. The intervention began with an analysis of the existing financial recording system. Subsequently, a VBA-based Excel format was designed to accommodate the business unit’s needs, such as daily cash records, stock control, and the management of reimbursements and taxes. Once the format was finalized, the team proceeded to input the data into the Manager.io application to generate automated financial reports. The final stage involved mentoring and system socialization to the store staff. The results show that the digitalization model improved internal transparency and efficiency, as well as enhanced the regularity of financial records, reporting processes, and staff understanding of digital accounting systems. This model can also be adopted by other MSMEs with similar conditions.